Hubungan gaya kepimpinan transformasional Pengetua dengan kepuasan kerja guru di sekolah menengah daerah Pasir Gudang - Abd. Majid, Intan Nor Farinie (2013)
This descriptive research aims to identify the relationship between transformational leadership style and the level of job satisfaction. A total of 345 teachers from secondary schools in Pasir Gudang were involved. Researchers have used the MLQ instrument (Multi Factor Leadership Questionnaire) to see transformational leadership style of principals and questionnaire Minnesota from Weiss (1967) is used as instrument to see teachers’ job satisfaction. The finding of the pilot study indicated that the instrument’s coefficient alpha is 0.742 to 0.838. Data from the survey were analysed using the Statistical Package of Social Sciences (SPSS) version 20.0, involving descriptive and inferential statistics of correlation only. Findings of the study show that the Individually Considerate is highly practised in transformational leadership. Meanwhile, the most dominant aspects of teachers’ job satisfaction is Opportunity to Advance in Your Profession. Correlation analysis also confirmed that the ideal influence and inspirational motivation has a significant relationship to job satisfaction. While the individual components of consideration and intellectual stimulation showed no significant relationship to job satisfaction. Finally, the study proposed several suggestions to relevant agencies or parties for further actions and for future research.